The numerical study on the sensitivity of different auto-conversion parameterization to CCN concentration - Li, Yi; Liu, Xiaoli; Yuan, Chaoyu (Frontiers in Environmental Science, 2023)
The auto-conversion from cloud droplet to raindrop is a process whereby rain drops formed by collision-coalescence of cloud droplets. As an important link connecting aerosol-cloud interaction, it has an important influence on the changes of cloud morphology and precipitation. In order to explore the sensitivity of auto-conversion schemes to cloud condensation nuclei (CCN) concentration, using the auto-conversion scheme in Thompson scheme (TH-AU) and Milbrandt-Yau scheme (MY-AU), we set four groups of CCN concentrations to simulate a strong convection process in Ningxia region of China. The results showed that: the sensitivity of different auto-conversion schemes to changes in CCN concentrations varies significantly, and the aerosol-induced changes in precipitation and convection are strongly dependent on the auto-conversion scheme. With the increase of CCN concentration, the cloud droplet mixing ratio increases and the particle size decreases, resulting in the decrease of the auto-conversion intensity for two schemes. Compared with Th-AU, MY-AU has lower auto-conversion intensity at the same CCN concentration, resulting in more freezing of supercooled water. Therefore, the increase of mixing ratio of snow and graupel particles in MY-AU is stronger than TH-AU with the increase of CCN concentration, and the graupel particle generation height of MY-AU is lower than that of TH-AU. In addition, the raindrop mixing ratio at the height of 4000-6000m decreased with the increase of CCN concentration in two schemes. Therefore, the warm rain process of MY-AU is strongly inhibited, and the cumulative precipitation as well as accumulated graupel on the ground decreases strongly with the increase of CCN concentration. Compared with MY-AU, the warm rain process of TH-AU was not significantly inhibited. So, the cumulative precipitation and graupel fall on the ground of TH-AU scheme increased when the CCN concentration was 50-2000cm-3, and slightly decreased when the CCN concentration was 2000-10000cm-3.